Socialization of Amendment Futsal Laws Of The Game 2020/2021 Edition at the Sports Teacher Working Group (KKGO) - Eko Prabowo; Rizky Nurulfa; Andri Irawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract: This dedication to the community activity was carried out for Physical Education teachers at the Sports Teacher Working Group (KKGO) in Bekasi Regency, West Java. Sports, especially the development of futsal in Indonesia, it is undeniable that futsal is one of the sports that is very popular with the community, especially at the student level. This issue is very good and important for physical education teachers who act as educators and coaches to develop themselves not only knowledge of techniques and tactics, but knowledge of the rules of the game. This community service activity uses the socialization method as a way to convey the material for the rules of the futsal game. The number of participants in the activity was 37 physical education teachers. 70.3% (26 people) rated this activity program very good and 29.7% (11 people) rated it good. The results of the needs of teachers for learning and futsal matches in schools are 56.8% (21 people) very suitable, 37.8% (14 people) are suitable and 5.4% (2 people) are quite suitable. The results of implementing this socialization material to learning and futsal competitions in schools were 67.6% (25 people) very interested, 27% (10 people) interested, and 5.4% (2 people) quite interested. The results of this activity are very good as education for physical education teachers who are also coaches of futsal at school. Keyword: Futsal, Laws Of The Game, KKGO